Singapore : 2010 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Singapore. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Strong policies, resilient markets, and an improved external environment have helped Singapore tide over the recession. Singapore has a strong track record of proactive and forward-looking economic policymaking. Fiscal policy has regained its traditional medium-term orientation. Official reserve accumulation has to be kept under review. Social safety nets are well placed. Singapore's exchange rate regime continues to serve the economy well, and the Monetary Authority of Singapore's exchange-rate-centered monetary framework has been an important source of stability in times of economic turbulence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet